Feed-Forward and Long Short-Term Neural Network Models for Power System State Estimation - Tuan-Ho Le (My University, 2024)
Feed-Forward and Long Short-Term Neural Network Models for Power System State Estimation
Keywords: Ước lượng trạng thái; Hệ thống điện; Feed-forward & LSTM